Evaluation of Changes in Students’ Perceptions of Scientific Article Writing Skills through a Cohort Survey - Yulisman, Hendra; Wardiah, Wardiah; Artika, Wiwit; Pada, Andi Ulfa Tenri; Nurina, Cut Intan Evtia (Indonesian Journal of Education Research (IJoER), 2025)
Purpose of the study: To evaluate the development of students’ perceptions of their ability to write scientific articles and to identify the parts of scientific articles that are most understood and most difficult to understand by students. Methodology: This cohort survey research was conducted by distributing questionnaires twice, namely in December 2024 and March 2025. The first survey was distributed via Microsoft Form during an online socialization event that focused on the writing of scientific articles from undergraduate theses. There were 67 students present at the event. The second survey was conducted in person during a socialization event that introduced scientific journals affiliated with the Biology Education Study Program at Faculty of Teacher Training and Education, Universitas Syiah Kuala. The event was attended by 68 students. The data obtained were subsequently analyzed using descriptive statistics. Main Findings: There has been a positive development in students’ perception of their ability to write scientific articles. In addition, this research successfully identified the parts of scientific articles that are most understood and those that are still difficult for students to comprehend. Novelty/Originality of this study: This research uses a longitudinal survey, specifically a cohort survey, to obtain a comprehensive evaluation of the development of students’ perceptions in writing scientific articles.